Applications of Anterior Segment Optical Coherence Tomography in Cornea and Ocular Surface Diseases. (19th September 2016) - Han, Sang Beom; Liu, Yu-Chi; Noriega, Karim Mohamed; Mehta, Jodhbir S.
Abstract : Optical coherence tomography (OCT) is a noncontact technology that produces high-resolution cross-sectional images of ocular tissues. Anterior segment OCT (AS-OCT) enables the precise visualization of anterior segment structure; thus, it can be used in various corneal and ocular surface disorders. In this review, the authors will discuss the application of AS-OCT for diagnosis and management of various corneal and ocular surface disorders. Use of AS-OCT for anterior segment surgery and postoperative management will also be discussed. In addition, application of the device for research using human data and animal models will be introduced.